Estimate cost for an electrical installation design using software / Rohaya Muhamad Rudzi - Muhamad Rudzi, Rohaya (2006)
The title of this project is estimate cost for an electrical installation design using software. This project concerns about how to automation and estimate costing for an electrical installation. Traditionally, costing for an electrical installation is usually using a calculator. These methods are wasting time and not efficiënt. By introducing new software, this problem can be solved. The software employed on the spreadsheet and Microsoft Access. By using this software, it can estimate the calculations required with manual methods instructions in the operating system teil the computer how to perform the type of functions. Beside that, it can integrate the drawing and cost for final costing of the project. By apply this software, it can optimization the cost and integrate the design until optimum values achieved. This software also used to calculate and recalculate cost in automatically without any error and more efficiënt. . The most important function that the software builds performs for the consultant are to solve problem far faster than otherwise and it will becomes easier.